Latina humor in the works of Sandra Cisneros - Tóth Zsófia Anna; Cisneros Sandra (Universidad de Szeged, Departamento de Estudios Hispánicos Szeged, 2020)
The paper discusses three works written by Sandra Cisneros, namely Woman Hollering Creek, The House on Mango Street and Caramelo, from the point of view of women’s humor. With the help of these works, it is argued that Cisneros uses Latina humor in order to highlight intersectional problems concerning her identity and to reveal important facts and features about/of Latino/a existence. The point is made that Cisneros uses comedy and humor to redeem the pain and suffering through laughter instead of utilizing the tragic mode of artistic expression, hence she is able to secure survival and solutions to problems instead of a tragic wallowing in negativity (which interpretive way could also have validity concerning the occurrences which are narrated).
Keywords: Bölcsészettudományok; Nyelvek és irodalom